2008
DOI: 10.1016/j.cell.2008.08.039
|View full text |Cite
|
Sign up to set email alerts
|

A Eukaryotic-like Ser/Thr Kinase Signals Bacteria to Exit Dormancy in Response to Peptidoglycan Fragments

Abstract: SUMMARY Bacteria can respond to adverse environmental conditions by drastically reducing or even ceasing metabolic activity. They must then determine that conditions have improved before exiting dormancy, and one indication of such a change is the growth of other bacteria in the local environment. Growing bacteria release muropeptide fragments of the cell wall into the extracellular milieu, and we report here that these muropeptides are potent germinants of dormant Bacillus subtilis spores. The ability of a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
524
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(549 citation statements)
references
References 50 publications
15
524
0
Order By: Relevance
“…In conclusion, our study establishes a clear correlation between reversible protein phosphorylation by the PrkC/PrpC pair and gliding motility in M. pneumoniae but does not assert that protein phosphorylation by PrkC drives the gliding motor. Rather, we suggest that PrpC and PrkC constitute part of a regulatory circuit comparable to that in B. subtilis wherein the phosphorylation of elongation factor Tu and other phosphoproteins influences aspects of sporulation and cell wall biosynthesis (18,20). Homologous eSTP/eSTK-associated regulation of swarming in Myxococcus xanthus, cell division in Mycobacterium tuberculosis, and virulence in Yersinia pseudotuberculosis have been previously reported (19), indicating that reversible protein phosphorylation is coupled to a diverse slate of functions in bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, our study establishes a clear correlation between reversible protein phosphorylation by the PrkC/PrpC pair and gliding motility in M. pneumoniae but does not assert that protein phosphorylation by PrkC drives the gliding motor. Rather, we suggest that PrpC and PrkC constitute part of a regulatory circuit comparable to that in B. subtilis wherein the phosphorylation of elongation factor Tu and other phosphoproteins influences aspects of sporulation and cell wall biosynthesis (18,20). Homologous eSTP/eSTK-associated regulation of swarming in Myxococcus xanthus, cell division in Mycobacterium tuberculosis, and virulence in Yersinia pseudotuberculosis have been previously reported (19), indicating that reversible protein phosphorylation is coupled to a diverse slate of functions in bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…PrpC and its homologs are often partnered with the cognate kinase PrkC, a highly conserved eukaryotic-like Ser/Thr kinase (eSTK). Mutant analysis in Bacillus subtilis has shown that homologs to these enzymes regulate sporulation and cell wall development by reversible phosphorylation (18)(19)(20). Similar reversible phosphorylation might occur in M. pneumoniae, where terminal organelle proteins HMW1 and HMW2 (MPN310) are phosphorylated in an ATP-dependent manner (21).…”
mentioning
confidence: 99%
“…Multiple reports show that STKs carrying PASTA domains play important regulatory roles in Mycobacterium and Corynebacterium. PASTA domains are known to bind peptidoglycan components and β-lactam antibiotics (21,32), and actinobacterial STKs carrying such domains (PknA and PknB) have been reported to phosphorylate several proteins involved in cell wall growth and cell division, including the mycobacterial DivIVA-orthologue Wag31 (e.g., refs. 24, 33-35).…”
Section: Diviva Phosphorylation Increases Dramatically When Cell Wallmentioning
confidence: 99%
“…20). For example, in B. subtilis, the STK PrkC controls germination of spores in response to muropeptides released from bacterial cell walls, and, in Streptococcus pneumoniae, the STK StkP is involved in coordination of growth and cell division (21,22). These two bacterial species have only two and one STKs, respectively, but the phylogenetic distribution of STKs among bacterial taxa is uneven; some groups encode only a few per genome whereas others have dozens-or, in some cases, even hundreds-of STK genes (23).…”
mentioning
confidence: 99%
“…Nevertheless, these A third type of molecule that can trigger spore germination is low-molecular-weight fragments of growing cell peptidoglycan (PG). These PG fragments trigger spore germination by activating the protein kinase PrkC (30,32). While spore PG differs in structure from growing cell PG, and thus cortical PG fragments might not activate PrkC, it still seemed worth examining whether this mechanism was responsible for spore-tospore communication during spore germination.…”
Section: Resultsmentioning
confidence: 99%